2010
DOI: 10.1128/jvi.00584-10
|View full text |Cite
|
Sign up to set email alerts
|

Productive Replication of vif -Chimeric HIV-1 in Feline Cells

Abstract: Nonprimate animal models of HIV-1 infection are prevented by missing cellular cofactors and by antiviral actions of species-specific host defense factors. These blocks are profound in rodents but may be less abundant in certain Carnivora. Here, we enabled productive, spreading replication and passage of HIV-1 in feline cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
79
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(83 citation statements)
references
References 98 publications
(121 reference statements)
4
79
0
Order By: Relevance
“…1, compare lanes 7 and 8). Interestingly, Rev expression stimulated VLP production Ͼ10-fold in cat (CRFK) and quail (QT35) cell types, a finding consistent with prior reports of significant Rev activity in nonhuman cell types other than those derived from rodents (43,(58)(59)(60). However, although hCRM1 exerted no effect on Rev activity in cat cells, VLP production in the avian cell line was enhanced a further ϳ10-fold when Rev and hCRM1 were expressed together ( Fig.…”
Section: Species-specific Regulation Of Hiv-1 Rev Activitysupporting
confidence: 80%
“…1, compare lanes 7 and 8). Interestingly, Rev expression stimulated VLP production Ͼ10-fold in cat (CRFK) and quail (QT35) cell types, a finding consistent with prior reports of significant Rev activity in nonhuman cell types other than those derived from rodents (43,(58)(59)(60). However, although hCRM1 exerted no effect on Rev activity in cat cells, VLP production in the avian cell line was enhanced a further ϳ10-fold when Rev and hCRM1 were expressed together ( Fig.…”
Section: Species-specific Regulation Of Hiv-1 Rev Activitysupporting
confidence: 80%
“…It is believed that FIV Vif makes a fundamental contribution to overcoming the restrictions imposed by fA3Z3 and fA3Z2-Z3 (23,47,63). FIV Vif colocalizes with the feline A3 proteins, targets them for proteasome degradation, and rescues the infectivity of the virus (47). The specific interactions between FIV Vif and the fA3 proteins are still unclear, and the precise mechanism of FIV Vif induced degradation of fA3s remains to be elucidated.…”
mentioning
confidence: 99%
“…Infectivity of Bet-deficient FFV is reduced not only by genomic deamination but also by an A3-induced reduction of particle release (28). The infectivity of Vif-deficient feline immunodeficiency virus (FIV) and feline leukemia virus (FeLV) is reduced by fA3Z3 and fA3Z2-Z3 (28,37) by induction of G3A hypermutation of the viral cDNA (37,47). The antiretroviral activities of the fA3Z2s are inhibited by the foamy virus accessory Bet protein (28), while the mechanism of FeLV against fA3s is unknown (38).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that binding detected by co-IPs is not a proper reporter for Vif-mediated counteraction affecting the protein levels. Indeed, several previous studies reported that binding of Vif and A3 is not the only determinant for complete Vif-medi- ated degradation (53,57,(83)(84)(85). Kitamura et al identified several residues between ␣2 and ␣3 helices of A3C binding to HIV-1 Vif (63).…”
Section: Discussionmentioning
confidence: 99%